Pengaruh Penggunaan Permainan Edukatif dalam Pembelajaran Kosakata Bahasa Inggris pada Anak Usia Pra-Sekolah - Hanifatur Rizqi; Eko Adi Sumitro (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the effect of using educational games on learning English vocabulary in pre-school children. The background of this research is based on the importance of learning English from an early age, where vocabulary mastery is a crucial basic component. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of 60 pre-school children who were randomly divided into experimental groups and control groups. The experimental group was given vocabulary learning using various educational games, while the control group used conventional methods. Data was collected through vocabulary tests before and after treatment, as well as observations during the learning process. The results of data analysis show that there is a significant increase in mastery of English vocabulary in the experimental group compared to the control group. These findings indicate that educational games can be an effective method in improving English vocabulary learning in pre-school children. This research suggests that educators consider the integration of educational games in the English language learning curriculum for early childhood.